Robotization in Industry and Agriculture - Giudice Baca, Victor (2022)
World Industries and Agriculture are in the process of Robotization. Agricultural robots, autonomous (driverless) tractors, with sunroofs are on the rise, and crop farming robots are growing. Harvesting robots have been found with 24 hands. In the Automotive Industry, robots are increasing more in Asia than in the US and Europe. Argentina develops precision agriculture. Brazil, a major producer of corn, wheat and cassava, is using agricultural robots for drip-irrigated plantations. In Peru, crops with solar panels are being developed in Arequipa. Likewise, the deserts of Ica are being conquered with Solar Panels. In Business Schools, study curricula are adapting to the Fourth Industrial Revolution.